CYTOKINE-GUIDED IMMUNOLOGICAL CORRECTION AFTER TOTAL KNEE ARTHROPLASTY IN RHEUMATOID ARTHRITIS: FIRST REAL-WORLD MULTICENTER STUDY FROM UZBEKISTAN - Anorboev , Maruf; Akhmedov, Khalmurad; Khujanazarov , Ilkhom (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This multicenter real-world study from Uzbekistan evaluated cytokine-guided postoperative immunological correction in patients with rheumatoid arthritis undergoing total knee arthroplasty. A total of 106 patients were stratified according to dominant cytokine profiles, including TNF-α, IL-6, and IL-1β, and received pathway-matched biologic therapy with csDMARDs. Over 52 weeks, significant improvements were observed in DAS28, HAQ-DI, VAS pain, CRP, ESR, and cytokine levels. Nearly half of the patients achieved remission, and most reached low disease activity. No prosthetic joint infections, implant failures, or deaths were recorded. These findings suggest that cytokine-guided personalized therapy may improve postoperative recovery, disease control, and safety in rheumatoid arthritis patients after total knee arthroplasty.Начало формы